2023
DOI: 10.1029/2022gl102207
|View full text |Cite
|
Sign up to set email alerts
|

The Dielectric Properties of Martian Regolith at the Tianwen‐1 Landing Site

Abstract: On Mars, compared to an airless body such as the Moon, the weathering layer ("regolith", a general term for the layer of fragmental and unconsolidated rock material, whether residual or transported and of highly varied character, that nearly everywhere forms the surface of the land and overlies or covers bedrock) underwent complicated geological processes in addition to weaker impact and space weathering modifications. A fuller understanding of the stratigraphy and properties of the martian regolith would unra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Furthermore, two tilted interfaces are constructed at the model bottom, with electrical parameters of r = 9.00 and σ = 2.61 × 10 −4 S/m. The recent research has indicated that the loss tangent value of Martian regolith at the Tianwen-1 landing site is 0.0174 +0.0053 −0.0053 [29]. The loss tangent value of 0.0174 is used to evaluate the conductivity of σ = 5.246 × 10 −5 .…”
Section: Forward Modelingmentioning
confidence: 99%
“…Furthermore, two tilted interfaces are constructed at the model bottom, with electrical parameters of r = 9.00 and σ = 2.61 × 10 −4 S/m. The recent research has indicated that the loss tangent value of Martian regolith at the Tianwen-1 landing site is 0.0174 +0.0053 −0.0053 [29]. The loss tangent value of 0.0174 is used to evaluate the conductivity of σ = 5.246 × 10 −5 .…”
Section: Forward Modelingmentioning
confidence: 99%
“…Due to the special nature of planetary exploration, the hyperbolic method is widely used in the relative permittivity estimation of the rover mounted GPR data. Researchers have utilised this method to calculate relative permittivity for the Martian Rover radar data, including "RIMFAX", the GPR carried by the Perseverance Rover [21]- [23] and the RoPeR mounted on the Zhurong Rover [24] [25].…”
Section: Introductionmentioning
confidence: 99%